" Aplicación de contabilidad comercial en “Papelería Silva” en la ciudad de Loja, periodo: septiembre - noviembre /2014 " - Rosales Vásquez, Viviana Karina (2015)
the requisites of the university to obtain the respective degree, it was develop this thesis called. “APLICACIÓN DE CONTABILIDAD COMERCIAL EN “PAPELERÍA SILVA” EN LA CIUDAD DE LOJA, PERIODO: SEPTIEMBRE - NOVIEMBRE /2014” Beside this, it was run in order to have a real appreciation of the financial situation of the business, so we can raise the necessary y solutions for the existing problems. We could fulfill with each of the objectives outlined in the project through the implementation, which started selecting the source documents of the months of Agot to octber 2014, which were reviewed and classified. To continue with the process was the need for an Initial Inventory to know the real value of assets, liabilities and patrimony. With this information and based on the respective chart of accounts and the manual account we continued with the accounting process, starting from the Initial Balance to obtain the respective Financial Statements. According to the results the business has a good income and the owner was advised to continue taking the accounting basis to be implemented for real control of her sales and if necessary perform a re-categorization of the fee the RISE, in order to avoid future fines.